Influencing Factors On Open Unemployment: A Case Study Of Malang Regency - Anisa Fadillah; Syamsul Huda; Putra Perdana (Cita konsultindo, 2024)
Indonesia's economy is growing with an annual growth rate of between 4.5 and 5.2 percent, with the main focus on development reforms to improve people's welfare, but as a developing country, Indonesia faces serious challenges related to unemployment, which directly impacts individuals and becomes a heavy burden. Malang Regency is the area with the fifth highest unemployment rate in East Java. The purpose of this study is to determine the influence of the Number of Population, Labor Force Participation Rate on the Open Unemployment Rate, Minimum Wage, Human Development Index on the Open Unemployment Rate in Malang Regency. The research method applied in this study is a quantitative descriptive approach with multiple linear regression analysis. The data used in the study is secondary data that has been obtained from the Central Statistics Agency (BPS) of Malang Regency. The data that has been collected is a time series of data starting from 2014 - 2023. The results of the study partially showed that the number of population, labor force participation and human development index had an effect on the open unemployment rate in Malang Regency, while drinking wages had no effect in Malang Regency